Dispersion stability and characterization of lead-free transparent dielectric glass frit - Oh, Young-Jei; Lee, Jin-Won (KOREAN ASSOC CRYSTAL GROWTH, INC, 2009)
The effect of solvents and dispersants on the slurry dispersion stability in tape castings of lead-free transparent Bi(2)O(3)-ZnO-BaO-Al(2)O(3) dielectric layers for plasma display panel (PDP) were studied. A comparative study of mechanical and optical properties of the green sheets fabricated with and without dispersion stabilizers was performed. The optimum dispersion stability, which was due to steric stabilization, was observed for a 1.5 wt% polyethylene glycol solution in methanol with 33.3% solid loading; the corresponding green sheet demonstrated the best mechanical and optical performance after firing. The green sheet prepared by dispersion stability had a stronger tensile strength of 6.6 kg/cm(2) (6.47 MPa) and more uniform microstructure than the green sheet prepared without dispersion stability (tensile strength of 4.6 kg/cm(2) (4.51 MPa)). The optimum result was obtained by fire processing a green sheet at 505 degrees C for 30 minutes; the dielectric layer obtained with 30 gm thickness on sodalime glass substrate had a transmittance of 81% at a reference wavelength of 550 nm without a yellowing phenomenon.